2015
DOI: 10.3390/microarrays5010002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Critical Region Responsible for Split Hand/Foot Malformation Type 3 (SHFM3) Phenotype through Systematic Review of Literature and Mapping of Breakpoints Using Microarray Data

Abstract: Split hand/foot malformation (SHFM) is a limb malformation with underdeveloped or absent central digital rays, clefts of hands and feet, and variable syndactyly of the remaining digits. There are six types of SHFM. Here, we report a boy with SHFM type 3 having normal 4th and 5th digits, absent 2nd and 3rd digits, and a 4th finger flexion deformity, as well as absent 2nd, 3rd and 4th toes bilaterally. His father, two paternal uncles, and two paternal first cousins have similar phenotype. Chromosome analysis sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…In 2015, Li et al identified the minimal critical region responsible for the SHFM3 phenotype in a series of 42 patients gathered from DECIPHER, previously published cases (PubMed) and a family with 6 affected individuals. Interestingly, they concluded that duplication of sequence in exon 1 of BTRC could be sufficient to the development of the SHFM3 phenotype and suggested that this may be via cis-acting or trans-acting effects on genes or regulatory sequences involved in the limb development pathway [26]. It is also interesting that patients harbouring wider duplications might also present with other limb malformations such as bilateral femoral hypoplasia but no SHFM [27].…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Li et al identified the minimal critical region responsible for the SHFM3 phenotype in a series of 42 patients gathered from DECIPHER, previously published cases (PubMed) and a family with 6 affected individuals. Interestingly, they concluded that duplication of sequence in exon 1 of BTRC could be sufficient to the development of the SHFM3 phenotype and suggested that this may be via cis-acting or trans-acting effects on genes or regulatory sequences involved in the limb development pathway [26]. It is also interesting that patients harbouring wider duplications might also present with other limb malformations such as bilateral femoral hypoplasia but no SHFM [27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, duplication of the homologous gene BTRC (MIM: 603482 ) is implicated in split hand-foot malformation. 9 Moreover, FBXW11 participates in the Wnt/β-catenin signaling pathway, 10 , 11 which is fundamentally important in eye and brain development 12 , 13 and digit patterning. 14
Figure 1 Phenotypes of Individuals 1, 2, 4, 5, and 7 (A–C) Individual 1 at age 13 years, showing bilateral ptosis related to the underlying ocular anomalies (A), contractures affecting the distal interphalangeal joints of the left 4 th and 5 th fingers (B), and a wide sandal gap, short terminal phalanges, contractures affecting the 4 th and 5 th toes, 2–3 toe syndactyly, and scarring from surgery removing the left supernumerary toe (C).
…”
Section: Main Textmentioning
confidence: 99%
“…Copy number gains encompassing BTRC are linked with developmental limb anomalies. 9 , 56 Drosophila with mutations in Slimb, the ortholog of both FBXW11 and BTRC , develop supernumerary limbs or ectopic legs and eye anomalies. 57 , 58 , 59 In mice, mutations of GLI transcription factors can cause multiple malformations, including polydactyly, anophthalmia, and coloboma.…”
Section: Main Textmentioning
confidence: 99%
“…Both siblings were homozygous for this variant, demonstrating the effectiveness of this approach for identifying the underlying genetic phenomena in disorders like this. Another paper in this Special Issue also demonstrated the use of SNP microarrays in analyzing a rare condition, namely split-hand/foot malformation (SHFM) [7]. This condition affects one in 8500–25,000 newborns, with characteristic limb malformations of hands and feet.…”
Section: Contributionsmentioning
confidence: 99%